ANALISIS DEKONSTRUKSI TOKOH TAKESHI DAN MITSUSABURO DALAM NOVEL SILENT CRY KARYA KENZABURO OE PERSPEKTIF JACQUES DERRIDA - Abd. Ghofur (Research Institute and Community Engagement of IAIN MADURA, 2015)
This article is a little result done by the writer, in which critical analisys discourse study as a tool to learn literature. It is Kenzaburo Oe’s writing, a Japan writer who got Pulitzer or noble in literature. It employs Jaques Derrida deconstructive theory, while the researcher focuses on binary opposition. When deconstruction used, it will expose inside of the text, furthermore it produces other meaning or different point of view from the real text.